2011
DOI: 10.4315/0362-028x.jfp-10-563
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Microbial Risk Assessment for Escherichia coli O157 on Lettuce, Based on Survival Data from Controlled Studies in a Climate Chamber

Abstract: The aims of the study were to determine the survival of Escherichia coli O157 on lettuce as a function of temperature and light intensity, and to use that information in a screening-level quantitative microbial risk assessment (QMRA) in order to evaluate risk-reducing strategies including irrigation water quality guidelines, rinsing, and holding time between last irrigation and harvest. Iceberg lettuce was grown in a climate chamber and inoculated with E. coli O157. Bacterial numbers were determined with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 40 publications
4
50
0
Order By: Relevance
“…Because of the time between irrigation and harvest, pathogenic bacteria can be reduced in numbers by UV radiation from sunlight, drying, or competition with commensal microbiota (Brandl and Amundson, 2008;Ottoson et al, 2011). Increasing the interval between the time of contamination and the point of harvest significantly decreased the likelihood that pathogenic and non-pathogenic strains of E. coli would be present in the harvested product (Fonseca et al, 2011;Moyne et al, 2011).…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the time between irrigation and harvest, pathogenic bacteria can be reduced in numbers by UV radiation from sunlight, drying, or competition with commensal microbiota (Brandl and Amundson, 2008;Ottoson et al, 2011). Increasing the interval between the time of contamination and the point of harvest significantly decreased the likelihood that pathogenic and non-pathogenic strains of E. coli would be present in the harvested product (Fonseca et al, 2011;Moyne et al, 2011).…”
Section: 3mentioning
confidence: 99%
“…There is no widespread agreement regarding the microbiological guidelines to be established for irrigation water but they should be preferably based upon risk assessment as recommended in WHO documents (http://www.who.int/water_sanitation_health/dwq/gdwq3rev/en/). An example of implementation is to be found in the Australian Water guidelines ( http://www.environment.gov.au/resource/national-waterquality-management-strategy-australian-guidelines-water-recycling-managing-0) and this may vary depending upon the time between irrigation and harvest and the type of irrigation method (Fonseca et al, 2011;Ottoson et al, 2011). In most cases, the enumeration of generic E. coli is used as an indicator organism as its presence relates to faecal pollution or failures in control measures.…”
Section: Summary Of the Most Important Preventive Measures At Primarymentioning
confidence: 99%
“…Foodborne pathogens present on the surface of fresh produce or of fresh cut produce may be inhibited by the indigenous microorganisms, and may be limited by available nutrients (Lopez-Velasco et al, 2012;Nguyen-The and Carlin, 2000); (Wood et al, 2010) demonstrated the bactericidal effect of UV radiation on enteric bacteria in the phyllosphere and there is also a significant effect of temperature and light intensity on survival of Escherichia coli O157 in lettuce (Ottoson et al, 2011). Prior to harvest, reduction in relative humidity caused death of Salmonella spp.…”
Section: Impact Of Other Factorsmentioning
confidence: 99%
“…Complex contextual factors in fresh produce primary production, production processes, trade, and logistic organization of the fresh produce supply chain also can affect the food safety risk of fresh produce and their derived food products (8,32,38,46). Recent food contamination events have highlighted the importance of the evaluation of risks associated with the food chain through exposure assessment, a key step in risk assessment.…”
mentioning
confidence: 98%